From the South and from the North? – Quilnus marcosi Heiss & Baena and Aradus angularis J. Sahlberg, two flat bug species new for Central Europe (Hemiptera, Heteroptera, Aradidae) - Gossner, Martin M.; Heckmann, Ralf; Moretti, Marco (Alpine Entomology, 2018)
The flat bug fauna of Switzerland is still insufficiently studied. We describe the first records of Aradus angularis J. Sahlberg, 1886 and Quilnus marcosi Heiss & Baena, 2006 (Heteroptera: Aradidae) in Switzerland from a burnt forest area in the canton Valais. These are also the first records for Central Europe. With these new records, the number of Aradidae species recorded in Switzerland increases to 21, and in the canton Valais to 16. A cantonal record list of aradid species in Switzerland and photographs of the two recently new recorded species are provided. The pyrophilous A. angularis shows a disjunct distribution pattern, disconnected from its known distributional range from Fennoscandia to Northeast China, which suggests that the species is a relict of the Ice Age in Central Europe. In contrast, the sub-Mediterranean Q. marcosi seems to have expanded its distributional range to the north-east or has previously gone unnoticed in Switzerland. The host plants of Q. marcosi include Pinus nigra and P. sylvestris.